Erratum: Development of Livelihood Skills through School-Based, Agripreneurship Projects Integrating Youth-Adult Partnerships: The Experiences of Youth Partners in Uganda - JIAEE Editors (Journal of International Agricultural and Extension Education, 2024)
Correction: The DOI of the article "Mukembo, S. C., Edwards, M. C., & Watters, C. E. (2020). Development of Livelihood Skills through School-Based, Agripreneurship Projects Integrating Youth-Adult Partnerships: The Experiences of Youth Partners in Uganda. Journal of International Agricultural and Extension Education, 27(4), 111-127” was incorrect as published. The correct DOI is: 10.5191//jiaee.2020.274111